2009
DOI: 10.1016/j.cell.2009.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin-1 Docks Secretory Vesicles to Syntaxin-1/SNAP-25 Acceptor Complexes

Abstract: Docking, the initial association of secretory vesicles with the plasma membrane, precedes formation of the SNARE complex, which drives membrane fusion. For many years, the molecular identity of the docked state, and especially the vesicular docking protein, has been unknown, as has the link to SNARE complex assembly. Here, using adrenal chromaffin cells, we identify the vesicular docking partner as synaptotagmin-1, the calcium sensor for exocytosis, and SNAP-25 as an essential plasma membrane docking factor, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
278
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(313 citation statements)
references
References 58 publications
32
278
1
2
Order By: Relevance
“…S6), thereby limiting the number of v-vesicles available for docking. Recently, it was suggested that synaptobrevin-2 is not required for the initial docking of synaptic vesicles to the plasma membrane in vivo (46,47). Our results show that large α-Syn oligomers specifically inhibit SNARE complex formation between synaptobrevin-2 and t-SNAREs after initial docking by other synaptic factors, such as synaptotagmin-1, in the neuron.…”
Section: Discussionsupporting
confidence: 56%
“…S6), thereby limiting the number of v-vesicles available for docking. Recently, it was suggested that synaptobrevin-2 is not required for the initial docking of synaptic vesicles to the plasma membrane in vivo (46,47). Our results show that large α-Syn oligomers specifically inhibit SNARE complex formation between synaptobrevin-2 and t-SNAREs after initial docking by other synaptic factors, such as synaptotagmin-1, in the neuron.…”
Section: Discussionsupporting
confidence: 56%
“…Synaptotagmin can bind to both syntaxin and SNAP-25, and fast neurotransmitter release requires synaptotagmin (Geppert et al 1994) probably prebound to assembled or partially assembled SNARE complexes (Schiavo et al 1997;Rickman et al 2006) so that Ca 2þ -induced interaction with phospholipids can occur rapidly (Xue et al 2008). It is still under debate how important synaptotagmin is in vesicle docking (de Wit et al 2009) and how it acts at the plasma membrane in fusion itself (Tang et al 2006;Hui et al 2009). Synaptotagmin could act as a brake on fusion that is relieved on Ca 2þ binding or have a positive role in membrane fusion (Chicka et al 2008).…”
Section: Synaptotagmins and Neurotransmitter Releasementioning
confidence: 99%
“…Using a proteoliposome clustering assay, they conclude that the R-SNARE Nyv1p is dispensable for vacuole docking, whereas the three Q-SNAREs are required. A very similar conclusion was recently reached for secretory vesicle docking in intact mammalian cells (12). This is an exciting convergence of new findings, which together suggest that establishing/stabilizing a cis3Q-SNARE complex may be a central step for docking to occur (see Fig.…”
mentioning
confidence: 52%
“…Evidence for a tethering step upstream of secretory vesicle fusion is sketchy and is therefore dimmed in the diagram. ment of SM-proteins for docking in the vacuole system as shown for Munc18-1 requirement in secretory vesicle docking (12). Although dispensable for the initial docking step, R-SNAREs remain essential for the downstream fusion reaction in both yeast vacuole and other systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation